The thymic cortical epithelium determines the TCR repertoire of IL‐17‐producing γδT cells. (13th March 2015) - Nitta, Takeshi; Muro, Ryunosuke; Shimizu, Yukiko; Nitta, Sachiko; Oda, Hiroyo; Ohte, Yuki; Goto, Motohito; Yanobu‐Takanashi, Rieko; Narita, Tomoya; Takayanagi, Hiroshi; Yasuda, Hisataka; Okamura, Tadashi; et al.
Abstract The thymus provides a specialized microenvironment in which distinct subsets of thymic epithelial cells (TECs) support T‐cell development. Here, we describe the significance of cortical TECs (cTECs) in T‐cell development, using a newly established mouse model of cTEC deficiency. The deficiency of mature cTECs caused a massive loss of thymic cellularity and impaired the development of αβT cells and invariant natural killer T cells. Unexpectedly, the differentiation of certain γδT‐cell subpopulations—interleukin‐17‐producing Vγ4 and Vγ6 cells—was strongly dysregulated, resulting in the perturbation of γδT‐mediated inflammatory responses in peripheral tissues. These findings show that cTECs contribute to the shaping of the TCR repertoire, not only of "conventional" αβT cells but also of inflammatory "innate" γδT cells.